Tính a^2+b^2+c^2- ab -bc-ac biết a+b+c=3
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có
\(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}=\frac{bc+ac+ab}{abc}=0\Rightarrow ab+bc+ac=0.\)
\(A=\frac{\left(bc\right)^3+\left(ac\right)^3+\left(ab\right)^3}{\left(abc\right)^2}\)
Ta có
\(\left(ab\right)^3+\left(bc\right)^3+\left(ac\right)^3-3\left(abc\right)^2=\)
\(=\left(ab+bc+ac\right)\left[\left(ab\right)^2+\left(bc\right)^2+\left(ac\right)^2-abbc-bcac-abac\right]=0\)
\(\Rightarrow\left(ab\right)^3+\left(bc\right)^3+\left(ac\right)^3=3\left(abc\right)^2\)
\(\Rightarrow A=\frac{3\left(abc\right)^2}{\left(abc\right)^2}=3\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{1}{\left(b-c\right)\left(a^2+ac-b^2-bc\right)}+\frac{1}{\left(c-a\right)\left(b^2+ab-c^2-ac\right)}+\frac{1}{\left(a-b\right)\left(c^2+bc-a^2-ab\right)}\)
\(=\frac{c-a}{\left(a-b\right)\left(b-c\right)\left(c-a\right)\left(a+b+c\right)}+\frac{a-b}{\left(a-b\right)\left(b-c\right)\left(c-a\right)\left(a+b+c\right)}\)
\(+\frac{b-c}{\left(a-b\right)\left(b-c\right)\left(c-a\right)\left(a+b+c\right)}\)
\(=0\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)